Phonon and magnetoelastic coupling in Al0.5Ga0.5FeO3: Raman, magnetization and neutron diffraction studies. Issue 13 (17th March 2020) - Mishra, K. K.; Shukla, R.; Krishna, P. S. R.; Babu, P. D.; Achary, S. N.; Katiyar, R. S.; Scott, J. F.
Abstract : Magnetoelastic behaviour in Al0.5 Ga0.5 FeO3 have been investigated using variable temperature neutron diffraction and Raman spectroscopy. Abstract : The intriguing coupling phenomena among spin, phonon, and charge degrees of freedom in materials having magnetic, ferroelectric and/or ferroelastic order have been of research interest for the fundamental understanding and technological relevance. We report a detailed study on structure and phonons of Al0.5 Ga0.5 FeO3 (ALGF), a lead-free magnetoelectric material, carried out using variable temperature dependent powder neutron diffraction and Raman spectroscopy. Neutron diffraction studies suggest that Al 3+ ions are distributed in one tetrahedrally (BO4 ) and three octahedrally (BO6 ) coordinated sites of the orthorhombic ( Pc 21 n) structure and there is no structural transition in the temperature range of 7–800 K. Temperature dependent field-cooled and zero-field-cooled magnetization studies indicate ferrimagnetic ordering below 225 K ( T N ), and that is reflected in the low temperature powder neutron diffraction data. An antiferromagnetic type arrangement of Fe 3+ ions with net magnetic moment of 0.13 μ B /Fe 3+ was observed from powder neutron diffraction analysis and it corroborates the findings from magnetization studies. At the magnetic transition temperature, no drastic change in lattice strain was observed, while significant changes in phonons were observed in the Raman spectra. The deviation of several mode frequencies from the standard anharmonicity model in the ferrimagnetic phase (below 240 K) is attributed to coupling effect between spin and phonon. Spin–phonon coupling effect is discernable from Raman bands located at 270, 425, 582, 695, 738, and 841 cm −1 . Their coupling strengths ( λ ) have been estimated using our phonon spectra and magnetization results. BO n ( n = 4, 6) libration (restricted rotation) mode at 270 cm −1 has the largest coupling constant ( λ ∼ 2.3), while the stretching vibrations located at 695 and 738 cm −1 have the lowest coupling constant ( λ ∼ 0.5). In addition to the libration mode, several internal stretching and bending modes of polyhedral units are strongly affected by spin ordering.